CSR in Family Business – Ethnocentric Meaning Socially Responsible? 1 - Marzena Starnawska; Magdalena Popowska (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The aim of this paper is to provide framework and key issues relevant for research on social responsibility of family business. From providing two theoretical approaches towards social responsibility such as social capital concept commenting on the familiness as a family firm resource and capability; and the stakeholder theory we move to the state of the art of family business. Then, we discuss heterogeneity among family firms show how it can determine their corporate social responsibility (CSR) approach. We also refer to family cohesion to show the role of the nature of exchange systems on the nexus of family and business systems. Following this unique feature, we provide some basic family firm characteristics (family involvement, ownership and influence) and we aim to outline how these characteristics determine social responsibility in family business by referring to the relevant literature. We summarize by suggesting the inward orientation of socially responsible behaviors among family firms, where family is a stakeholder at stake. As a result, non-economic goals matter in long term meaning preservation of family ties or transgenerational value creation.